Extended First Harmonic Approximation in Case of LLCC Converters with Capacitive Output Filter - Bucher, Alexander; Dürbaum, Thomas (15th IEEE Mediterranean Electrotechnical Conference (MELECON), 2010)
The analysis of resonant converters is in general more cumbersome than in case of PWM converters, as often a multitude of modes has to be regarded and resonant oscillations with durations impossible to calculate directly are encountered. Therefore, approximations are required in order to facilitate the design process. An extended approximation in the frequency domain for the steady-state solution of the multi-resonant LLCC converter with capacitive output filter is presented in this paper, with a new degree of simplification regarding the resulting closed-form solution. By means of this approximation, the design of the fourth-order resonant LLCC converter is significantly simplified, providing a tool for rapid simulation combined with a very high accuracy. The accuracy of the investigated approach was double-checked by means of exact calculations. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.extend